10 W mid-IR optical parametric oscillator pumped by a passively Q-switched Ho:YAG ceramic laser. (12th January 2016) - Yuan, Jin-He; Duan, Xiao-Ming; Yao, Bao-Quan; Li, Jiang; Li, Chao-Yu; Pan, Yu-Bai
Abstract: We report on a ZnGeP2 (ZGP) optical parametric oscillator (OPO) pumped by a Cr 2+ :ZnS saturable absorbed passively Q-switched (PQS) Ho:YAG ceramic laser. The maximum output power of the ZGP OPO was 10 W at a 27.4 W incident PQS Ho:YAG ceramic laser, corresponding to a slope efficiency of 41.3% with respect to the incident pump power. The minimum mid-IR pulse width of 21 ns in 3.8 and 4.6 μ m was obtained from the ZGP OPO. The beam quality was measured to be M 2 < 3.22.